Comparison of Elderly Men with Low and Elevated Chronic Systemic Inflammation in Indices of Strength, Oxidative Stress and Inflammation - Draganidis, Δημήτριος; Poulios, Αθανάσιος; Laschou, Βασιλική Κ.; Tzatzakis, Θεοφάνης; Papanikolaou, Κωνσταντίνος; Kritikos, Σάββας; Deli, Χαρίκλεια; Georgakouli, Καλλιόπη; Avloniti, Αλεξάνδρα; Pappas, Άγγελος; Jamurtas, Αθανάσιος Ζ.; Fatouros, Ιωάννης Γ. (Inquiries in Physical Education and Sport, 2018)
The aim of the study was to examine differences among elderly men with low and elevated chronic systemic inflammation (CSI) in indices of the immune system, oxidative stress, antioxidant capacity and strength of the upper and lower body. A total of thirty-three, healthy, elderly men aged 65-75 years were included in the study and grouped as either ″low‶ CSI (LCSI: n=16; hs-CRP: < 1 mg/L) or ″elevated‶ CSI (ECSI: n=17; hs-CRP: > 1 mg/L) according to their serum levels of high-sensitivity CRP (hs-CRP). All participants were assessed for anthropometrics, body composition via Dual Emission X-ray Absorptiometry (DXA), handgrip strength and lower limb muscle strength on a leg extension machine. Blood samples were also collected for the determination of white blood cells (WBC), granulocytes (GRA), monocytes (MON) and lymphocytes (LYM) concentration as well as for the measurement of protein carbonyls (PC) and total antioxidant capacity (TAC) in serum. ECSI was characterized by almost a 4-fold greater hs-CRP value compared to LCSI (ECSI: hs-CRP = 0.6±0.1 mg/L vs LCSI: hs-CRP = 2.3±0.8 mg/L, p=0.00). ECSI and LCSI were comparable in terms of anthropometric characteristics, body mass index, fat percent, fat mass, fat free mass, lean body mass as well as in handgrip and lower limb muscle strength. Moreover, no differences were observed among groups in WBC, GRA, MON and LYM counts and in PC concentration. In contrast, significant differences observed between groups in TAC, with LCSI displaying a greater antioxidant capacity than ECSI by 60% (p<0.05). In conclusion, white blood cell counts and protein carbonyl concentration as well as muscle strength of the lower and upper body are not different among elderly men with ″low‶ CSI and ″elevated‶ CSI. However, those with low levels of CSI are characterized by a greater antioxidant capacity compared to their counterparts with elevated CSI.